2023
DOI: 10.1038/s42003-023-04858-3
|View full text |Cite
|
Sign up to set email alerts
|

Orai, RyR, and IP3R channels cooperatively regulate calcium signaling in brain mid-capillary pericytes

Abstract: Pericytes are multifunctional cells of the vasculature that are vital to brain homeostasis, yet many of their fundamental physiological properties, such as Ca2+ signaling pathways, remain unexplored. We performed pharmacological and ion substitution experiments to investigate the mechanisms underlying pericyte Ca2+ signaling in acute cortical brain slices of PDGFRβ-Cre::GCaMP6f mice. We report that mid-capillary pericyte Ca2+ signalling differs from ensheathing type pericytes in that it is largely independent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
1
5
1
Order By: Relevance
“…S2C, D) or in vivo (Fig. 5E), similar to a recent report in brain slices (26). However, Pyr3 reduced the amplitude of Ca 2+ events within the soma of capillary pericytes in brain slices (Fig.…”
Section: L-type Vgcc and Trpc3 Channel Blockers Affect Capillary Peri...supporting
confidence: 89%
See 4 more Smart Citations
“…S2C, D) or in vivo (Fig. 5E), similar to a recent report in brain slices (26). However, Pyr3 reduced the amplitude of Ca 2+ events within the soma of capillary pericytes in brain slices (Fig.…”
Section: L-type Vgcc and Trpc3 Channel Blockers Affect Capillary Peri...supporting
confidence: 89%
“…GCaMP6s positive capillary pericytes were identified more than 5 branches from the penetrating arteriole. Recent studies of capillary pericyte Ca 2+ events in brain slices have found conflicting effects of L-type Ca 2+ channel blockers and no effect of Pyr3 on Ca 2+ event frequency (25,26). Therefore, we conducted both brain slice pharmacology experiments with nimodipine (1 µM) and Pyr3 (3 µM; Fig.…”
Section: L-type Vgcc and Trpc3 Channel Blockers Affect Capillary Peri...mentioning
confidence: 99%
See 3 more Smart Citations